Prevention of Fraud: Using the Concept of Istikhlaf Approach for Public Accountants - Husna, Asmaul; Siregar, Saparuddin; Arif Lubis, Fauzi (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to explore the effectiveness of the istikhlaf concept approach in fraud prevention among public accountants. Istikhlaf, which refers to the concept of leadership and responsibility from an Islamic perspective, offers an ethical approach that can strengthen integrity and honesty in the accounting profession. This study uses a quantitative method by collecting data through questionnaires distributed to 63 public accountants in various public accounting firms in Medan city. Data analysis is conducted using the Partial Least Square (PLS) analysis method to determine the relationship between the implementation of the istikhlaf concept and the reduction of fraud incidents. The results of the study show that there is a significant positive correlation between the implementation of the istikhlaf concept and fraud prevention. Accountants who adopt the principles of istikhlaf tend to exhibit more ethical behavior and are less involved in fraudulent actions. These findings indicate that the integration of strong moral and ethical values, as promoted in the istikhlaf concept, can play an important role in fraud prevention efforts in the public accounting profession. This study suggests that public accountants consider implementing training programs that incorporate the istikhlaf concept to enhance ethical awareness and responsibility among accountants. Thus, the results of this study not only contribute to the academic literature on fraud prevention but also provide practical recommendations for practitioners in improving professional integrity.